تقويم الأداء المالي للمصارف الإسلامية والتقليدية الأردنية باستخدام مؤشرات نموذج "CAMEL" (دراسة تحليلية مقارنة) - الغصين, راغب; نشواتي, محمد عمار (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تهدف هذه الدراسة إلى تقويم الأداء المالي للمصارف الإسلامية والتقليدية الأردنية ومقارنته باستخدام المؤشرات المالية الخمسة لنموذج "CAMEL" المتمثلة بـ: مؤشر كفاية رأس المال، مؤشر جودة الأصول، مؤشر جودة الإدارة، مؤشر إدارة الربحية، ومؤشر إدارة السيولة وذلك بهدف اكتشاف أي من المصرفيين الإسلامي أو التقليدي حقق أداء أفضل من الآخر بالإضافة إلى دراسة مدى انعكاس الأداء المالي على مستوى الثقة العامّة لجمهور العملاء. ولتحقيق هذا الغرض تم اختيار جميع المصارف الإسلامية والتقليدية الأردنية (ثلاثة عشر مصرفاً تقليدياً، مصرفيين اسلاميين) كعينة للدراسة خلال الفترة (2006-2012)، وتم توظيف اختبار t-testلدراسة معنوية الفروق بين متوسطات النسب المالية وتحليل الانحدار الخطي المتعدد لدراسة أثر مؤشرات الأداء المالي منفردة ومجتمعة على مستوى ثقة العامّة. توصلت الدراسة إلى تحقيق المصارف التقليدية لأداء مالي أفضل من المصارف الإسلامية وإلى أن مستوى الثقة العامّة لجمهور العملاء في المصارف الإسلامية ينشأ بشكل رئيسي من الأداء المالي المتحقق لها على عكس ما تم التوصل اليه بالنسبة للمصارف التقليدية. This study aims to evaluate and compare the financial performance of the Jordanian Islamic and conventional banks using the five financial indicators of the "CAMEL" method represented by: Capital Adequacy index, Asset Quality index, Management Quality index, Profitability index, and the Liquidity index. This comparison will detect which of the two banks Islamic or Conventional achieves a better performance than the other. In order to study the reflection of financial performance on customers at the level of public trust, and to achieve these purposes, we select a total of thirteen Jordanian Conventional banks and two Islamic banks as a sample for this study during the period of (2006-2012). We employ a test “t-test” to study the significance of the differences between the averages of financial ratios and the use of multiple linear regression analysis to show the impact of financial performance indicators individually and collectively on the level of public trust. The result of this study clearly shows that Conventional banking achieves a better financial performance than Islamic banking, although the level of public trust of customers in Islamic banking stems mainly from its achieved financial performance, contrary to what has been obtained during this study for Conventional banking.